After God, After Islam - Muhammad Endy Saputro (Al-Ulum, 2011)
This article aimed to examine the Cupittâ€™s conception in the light of Islamic paradigm. It is done by identifying negative impacts of postmodernism toward the existence of religion. Religion, in Don Cuppit view is alive in the term of â€œvalueâ€, â€œprivate realmâ€, â€œpersonal faithâ€ and â€œcountercultureâ€. Although Islam came from hundreds centuries ago, it does not mean that authentic Islam is Islam in the past. Islam in the past, Islam in the present and Islam in the future are different. Islam is not timeless doctrine, but changeable expression. Time is running; and Islam demanded to contextualize itself dynamically.